2023
DOI: 10.1021/acs.energyfuels.3c01538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Dominant Mechanisms of Oil Recovery by Low Salinity Water in Fractured Carbonates

Razieh Kashiri,
Arman Garapov,
Peyman Pourafshary

Abstract: The spontaneous imbibition process involves the fluid flow driven by gravity and capillary forces between the matrix and fractures, which is a critical mechanism in oil production in naturally fractured reservoirs (NFRs). Previous studies have explored how various rock and fluid parameters, such as temperature, permeability, connate water saturation, and initial wettability, impact the performance of low salinity water in NFRs using spontaneous imbibition tests. In this particular study, we aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…16−18 Additionally, IFT reduction tends to correlate with an increase in pH resulting from mineral dissolution in carbonate rocks, thereby leading to the formation of in situ surfactants from carboxyl compounds in crude oil. 19 Changes in wettability are closely related to the presence of divalent ions in the brine. A small amount of divalent cations exhibits a "bridging effect" when combined with the polar components in crude oil, adsorbing on the surface of the rock, and altering wettability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16−18 Additionally, IFT reduction tends to correlate with an increase in pH resulting from mineral dissolution in carbonate rocks, thereby leading to the formation of in situ surfactants from carboxyl compounds in crude oil. 19 Changes in wettability are closely related to the presence of divalent ions in the brine. A small amount of divalent cations exhibits a "bridging effect" when combined with the polar components in crude oil, adsorbing on the surface of the rock, and altering wettability.…”
Section: Introductionmentioning
confidence: 99%
“…The study of low-salinity waterflooding primarily focuses on interfacial tension (IFT), wettability, and zeta potential. IFT reduction predominantly occurs due to the interaction of natural surfactants such as asphaltene and colloids in crude oil with trace amounts of Ca 2+ and Mg 2+ in water. These ions are adsorbed at the oil/water interface, changing IFT. , However, studies have shown that IFT is not the primary mechanism for low-salinity waterflooding, with reductions typically limited to 3–4 mN/m. Additionally, IFT reduction tends to correlate with an increase in pH resulting from mineral dissolution in carbonate rocks, thereby leading to the formation of in situ surfactants from carboxyl compounds in crude oil . Changes in wettability are closely related to the presence of divalent ions in the brine.…”
Section: Introductionmentioning
confidence: 99%